1982
DOI: 10.1159/000182453
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Intestinal Fat Absorption in Chronic Renal Failure

Abstract: We performed oral fat loading tests in 10 patients with chronic renal failure (CRF) on hemodialysis (5 children and 5 adults). Fat absorption was measured by hourly determination of serum triglycerides (TG), cholesterol (CHOL), and lipoproteins (LP) after oral administration of a ‘milkshake’ containing 50 g of fat of dairy origin. 10 age-matched healthy volunteers with normal fasting serum TG levels and 10 subjects with fasting hypertriglyceridemia served as controls. Mean fasting serum TG levels in CRF patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Our findings are not that surprising considering the broad range of uremia-related gastrointestinal abnormalities reported in literature, including gastrointestinal motility disorders [37][38][39][40][41], small bowel bacterial overgrowth [42,43], gastric hypochlorhydria [26,37,44], and uremic pancreopathy [44][45][46][47][48][49][50][51][52]. Each of them could theoretically disturb protein digestion and/or absorption.…”
Section: Discussionmentioning
confidence: 80%
“…Our findings are not that surprising considering the broad range of uremia-related gastrointestinal abnormalities reported in literature, including gastrointestinal motility disorders [37][38][39][40][41], small bowel bacterial overgrowth [42,43], gastric hypochlorhydria [26,37,44], and uremic pancreopathy [44][45][46][47][48][49][50][51][52]. Each of them could theoretically disturb protein digestion and/or absorption.…”
Section: Discussionmentioning
confidence: 80%
“…Whereas there is no widespread indication from clinical practice of a significant alteration in intestinal fat absorption [109], this may in fact occur [110,111]. Regardless, in studies of patients with CRI, there is a greater rise and an abnormally prolonged increase in circulating triglycerides postprandially [112,113].…”
Section: Postprandial Lipoproteins and Effects Of Crimentioning
confidence: 99%
“…There are only a few studies that address cholesterol homeostasis and its relationship with cardiovascular risk within CKD or HD populations. CKD patients were reported to have impaired intestinal fat absorption [34]. In a study on eight HD patients, investigators reported that HD patients demonstrated significantly lower fractional cholesterol synthesis (lathosterol) and lower lathosterol to cholesterol ratio compared to healthy controls [16].…”
Section: Discussionmentioning
confidence: 99%